Associations between compulsive buying and substance dependence/abuse, major depressive episodes, and generalized anxiety disorder among men and women. Issue 4 (1st October 2016) - Zhang, Chenshu; Brook, Judith S.; Leukefeld, Carl G.; Brook, David W.
ABSTRACT: The objective of this study was to examine the associations between compulsive buying and substance dependence/abuse, major depressive episodes, and generalized anxiety disorder at the mean age of 43. Participants came from a community-based random sample of residents in 2 New York counties in 1975 ( N = 548). The participants were followed from adolescence to early midlife. The mean age of participants at the most recent interview was 43.0 (standard deviation = 2.8). Of the participants, 55% were females. Over 90% of the participants were Caucasian. The prevalence of substance dependence/abuse, major depressive episodes, and generalized anxiety disorder (during the past 5 years before the interviews) was 6.6, 13.7, and 11.5%, respectively. Logistic regression analyses showed that compulsive buying was significantly associated with substance dependence/abuse (adjusted odds ratio = 1.60), major depressive episodes (adjusted odds ratio = 1.70), and generalized anxiety disorder (adjusted odds ratio = 1.63), despite controlling for substance dependence/abuse, major depressive episodes, and generalized anxiety disorder, respectively, at the mean age of 37, and demographic factors. Since the study sample is limited to predominantly Caucasian participants (over 90%) with a close association to a small geographic area, the findings may not be generalizable to racial/ethnic minority groups or individuals living in other parts of the country. Nevertheless, it is important that clinicians treating substance dependence/abuse, major depressive episodes, and generalized anxiety disorder consider the role of compulsive buying.